Exhaled SARS-CoV-2 RNA viral load kinetics measured by facemask sampling associates with household transmission. (February 2023) - Pan, Daniel; Williams, Caroline M.; Decker, Jonathan; Fletcher, Eve; Sze, Shirley; Assadi, Sara; Haigh, Richard; Saleem, Baber; Nazareth, Joshua; Garton, Natalie J.; Pareek, Manish; Barer, Michael R.
Abstract: Objectives: No studies have examined longitudinal patterns of naturally exhaled SARS-CoV-2 RNA viral load (VL) during acute infection. We report this using facemask sampling (FMS) and assessed the relationship between emitted RNA VL and household transmission. Methods: Between December 2020 and February 2021, we recruited participants within 24 hours of a positive RT-qPCR on upper respiratory tract sampling (URTS) (day 0). Participants gave FMS (for 1 hour) and URTS (self-taken) on seven occasions up to day 21. Samples were analysed by RT-qPCR (from sampling matrix strips within the mask) and symptom diaries were recorded. Household transmission was assessed through reporting of positive URTS RT-qPCR in household contacts. Results: Analysis of 203 FMS and 190 URTS from 34 participants showed that RNA VL peaked within the first 5 days following sampling. Concomitant URTS, FMS RNA VL, and symptom scores, however, were poorly correlated, but a higher severity of reported symptoms was associated with FMS positivity up to day 5. Of 28 participants who had household contacts, 12 (43%) reported transmission. Frequency of household transmission was associated with the highest (peak) FMS RNA VL obtained (negative genome copies/strip: 0% household transmission; 1 to 1000 copies/strip: 20%; 1001 to 10 000 copies/strip: 57%; >10 000 copies/strip: 75%; p = 0.048; age adjusted OR of household transmission per log increase in copies/strip: 4.97; 95% CI, 1.20–20.55; p = 0.02) but not observed with peak URTS RNA VL. Discussion: Exhaled RNA VL measured by FMS is highest in early infection, can be positive in symptomatic patients with concomitantly negative URTS, and is strongly associated with household transmission.